Prevalence of work-related musculoskeletal disorders among farmers in Pancasari Village, Sukasada District, Buleleng Regency: a preliminary study - Anggreni, Kadek Novi; Made Hendra Satria Nugraha; Ari Wibawa (Kinetic and Physiotherapy Comprehensive, 2023)
Background: Farmers are professionals who work actively in processing agricultural land. Farmers use physical strength to carry out all agricultural land activities, from seedling to harvesting. The daily work of farmers with high frequency in the long term can increase the risk of musculoskeletal systems called musculoskeletal disorders (MSDs). Methods: This study used analytic descriptive research with data collection techniques in the cross-sectional study. Data was collected in May 2022 using the Nordic Body Map (NBM) questionnaire and interviews. The analysis method used the univariate software IBM SPSS Statistics 26 to describe the characteristics of the variables. Results: Complaints experienced by research respondents with a score of 2 participated in the lower neck area (37.5%), right calf (35%), a score of 3 experienced in the waist area (22.5%), left knee and right knee (20%), a score of 4 was experienced in the waist area (35.5%). Respondents reported the risk of musculoskeletal issues, with 32 people in the low category and 8 in the medium category. Conclusion: According to the questionnaire responses, the most common complaints were with the lower back, knees, lower neck, and shoulders. Musculoskeletal diseases are mainly in the low-risk category among farmers.